Design and evaluation of tadpole-like conformational antimicrobial peptides - Tang, Ziyi (2024)
Antimicrobial peptides are promising alternatives to conventional antibiotics. Herein, we report a class of "tadpole-like" peptides consisting of an amphipathic α-helical head and an aromatic tail. A structure-activity relationship (SAR) study of "tadpole-like" temporin-SHf and its analogs revealed that increasing the number of aromatic residues in the tail, introducing Arg to the α-helical head and rearranging the peptide topology dramatically increased antimicrobial activity. Through progressive structural optimization, we obtained two peptides, HT2 and RI-HT2, which exhibited potent antimicrobial activity, no hemolytic activity and cytotoxicity, and no propensity to induce resistance. NMR and molecular dynamics simulations revealed that both peptides indeed adopted "tadpole-like" conformations. Fluorescence experiments and electron microscopy confirmed the membrane targeting mechanisms of the peptides. Our studies not only lead to the discovery of a series of ultrashort peptides with potent broad-spectrum antimicrobial activities, but also provide a new strategy for rational design of novel "tadpole-like" antimicrobial peptides.